Peanut‐based ready‐to‐use therapeutic food: how acceptable and tolerated is it among malnourished pregnant and lactating women in Bangladesh?. Issue 4 (6th May 2013) - Ali, Engy; Zachariah, Rony; Shams, Zubair; Manzi, Marcel; Akter, Tajmary; Alders, Petra; Allaouna, Malik; Delchevalerie, Pascale; Harries, Anthony.D.
Abstract Within a Medecins Sans Frontieres's nutrition programme in Kamrangirchar slum, Dhaka, Bangladesh this study was conducted to assess the acceptability of a peanut‐based ready‐to‐use therapeutic food (RUTF) – Plumpy'nut® (PPN) among malnourished pregnant and lactating women (PLW). This was a cross‐sectional survey using semi‐structure questionnaire that included all PLW admitted in the nutrition programme, who were either malnourished or at risk of malnutrition and who had received PPN for at least 4 weeks. A total of 248 women were interviewed of whom 99.6% were at risk of malnutrition. Overall, 212 (85%) perceived a therapeutic benefit. Despite this finding, 193 (78%) women found PPN unacceptable, of whom 12 (5%) completely rejected it after 4 weeks of intake. Reasons for unacceptability included undesirable taste (60%) and unwelcome smell (43%) – more than half of the latter was due to the peanut‐based smell. Overall, 39% attributed side effects to PPN intake including nausea, vomiting, diarrhoea, abdominal distension and pain. Nearly 80% of women felt a need to improve PPN – 82% desiring a change in taste and 48% desiring a change in smell. Overall, only 146 (59%) understood the illustrated instructions on the package. Despite a perceived beneficial therapeutic effect, only two in 10 women found PPN acceptable for nutritional rehabilitation. We urge nutritional agencies and manufacturers to intensify their efforts towards developing more RUTF alternatives that have improved palatability and smell for adults and that have adequate therapeutic contents for treating malnourished PLW in Bangladesh.